A new correlation for the prediction of critical quality in tubes. (January 2021) - Wu, Wanze; Sun, Baozhi; Shi, Jianxin; Yu, Xiang; Zhao, Zhirui
Highlights: A high applicability and accuracy correlation for predicting critical quality is proposed. The influence of multiple factors are fully considered. The applicable range and accuracy of different correlations are compared. Suggestions on selecting the correlations for predicting critical quality under different working conditions are given. Abstract: In this paper, dryout phenomenon of steam-liquid two-phase flow in vertical tube is studied. Based on Becker's experimental data, 393 points of dryout data with pressure ranging from 2.9 to 20.1 MPa, mass flow rate ranging from 496 to 3120 kg/(m 2 s), heat flux less than 1268 kW/m 2 and pipe diameter ranging from 10 to 24.7 mm are re-fitted, and a new correlation for predicting the critical quality is proposed. The MAE of the new correlation is 7.2% when predicting the Becker's data. It also positively correlated with other databases of steam-liquid critical quality. However, the prediction accuracy of the new correlation is relatively low for refrigerant and deformation channel, which will be further revised in future work.